The reciprocity of skeletal muscle and bone: an evolving view from mechanical coupling, secretory crosstalk to stem cell exchange - Sui, Hao; Dou, Jinfeng; Shi, Bing; Cheng, Xu (Frontiers in Physiology, 2024)
Introduction: Muscle and bone constitute the two main parts of the musculoskeletal system and generate an intricately coordinated motion system.The crosstalk between muscle and bone has been under investigation, leading to revolutionary perspectives in recent years. Method and Results: In this review, the evolving concept of muscle-bone interaction from mechanical coupling, secretory crosstalk to stem cell exchange was explained in sequence.The theory of mechanical coupling stems from the observation that the development and maintenance of bone mass are largely dependent on musclederived mechanical loads, which was later proved by Wolff's law, Utah paradigm and Mechanostat hypothesis. Then bone and muscle are gradually recognized as endocrine organs, which can secrete various cytokines to modulate the tissue homeostasis and remodeling to each other. The latest view presented muscle-bone interaction in a more direct way: the resident mesenchymal stromal cell in the skeletal muscle, i.e., fibro-adipogenic progenitors (FAPs), could migrate to the bone injury site and contribute to bone regeneration. Emerging evidence even reveals the ectopic source of FAPs from tissue outside the musculoskeletal system, highlighting its dynamic property.FAPs have been established as the critical cell connecting muscle and bone, which provides a new modality to study inter-tissue communication.A comprehensive and integrated perspective of muscle and bone will facilitate in-depth research in the musculoskeletal system and promote novel therapeutic avenues in treating musculoskeletal disorders.